2017
DOI: 10.1167/iovs.17-22319
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Staphylomas in Pathologic Myopia Imaged by Widefield Optical Coherence Tomography

Abstract: PURPOSE. To examine posterior staphylomas by widefield optical coherence tomography (WF-OCT) and three-dimensional magnetic resonance imaging (3D-MRI).METHODS. Highly myopic patients (myopic refractive error >8.0 diopters or axial length >26.5 mm) who had previously undergone orbital 3D-MRI were examined by WF-OCT. RESULTS.The study included 100 eyes of 57 patients with a mean age of 67.9 6 10.7 years (range, 44-85 years) and mean axial length of 30.0 6 2.3 mm (range, 25.1-36.5 mm). All staphylomas detected on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 24 publications
5
100
1
Order By: Relevance
“…Contour abnormalities of the choroid and sclera are well seen using EDI and SS OCT, and even more so in high myopia where the penetration is deeper due to the thinner choroid and relatively depigmented RPE. These include posterior staphyloma,[ 96 97 98 ] dome-shaped macula. [ 60 99 100 101 ] peripapillary and macular intrachoroidal cavitations,[ 61 62 ] and optic pits and colobomas[ 102 103 104 ]…”
Section: Choroidal Imagingmentioning
confidence: 99%
“…Contour abnormalities of the choroid and sclera are well seen using EDI and SS OCT, and even more so in high myopia where the penetration is deeper due to the thinner choroid and relatively depigmented RPE. These include posterior staphyloma,[ 96 97 98 ] dome-shaped macula. [ 60 99 100 101 ] peripapillary and macular intrachoroidal cavitations,[ 61 62 ] and optic pits and colobomas[ 102 103 104 ]…”
Section: Choroidal Imagingmentioning
confidence: 99%
“…17 Later, Ohno-Matsui et al 18 using three-dimensional magnetic resonance imaging (3D-MRI) and ultra-widefield fundus imaging proposed another classification into 6 types, based on the shape, location and shape of the staphyloma. Shinohara et al 19 have recently concluded that widefield OCT may replace 3D-MRI in assessing posterior staphylomas. In our case, patients were examined with posterior OCT with 6 radial scans on the 6-mm central macular area and those diagnosed with posterior staphyloma were classified as type IV and V according to the Ohno-Matsui et al 18 classification.…”
Section: Methodsmentioning
confidence: 99%
“…The authors found that WF OCT could provide high-resolution images, potentially replacing 3D-MRI in assessing PS. 24 …”
Section: Posterior Staphilomamentioning
confidence: 99%